Perceived Usefulness, Ease of Use, And Intention to Utilize Online Tools for Learning Among College of Education Students - Linus, Adefuye Adetayo; Aladesusi, Gboyega Ayodeji; Monsur, Ishola Adebayo; Elizabeth, Fasina Joke (Indonesian Journal of Multidiciplinary Research, 2025)
The adoption of online instructional tools has gained significant attention in higher education, particularly in Colleges of Education. This study investigated students' perception, ease of use, and intention to utilize online instructional tools for learning in North Central Nigeria. A descriptive correlational research design was employed, and data were collected from a representative sample of College of Education students using a structured questionnaire. The findings indicated a generally positive perception of online instructional tools among students. Additionally, students perceive these tools as easy to use, which further reinforces their willingness to adopt them for learning. The study also revealed that students demonstrated a strong positive intention toward utilizing online tools in their academic activities. Furthermore, a robust positive correlation was identified between students' perception of online instructional tools and their perceived ease of use, suggesting that favorable perceptions significantly influence usability. These findings underscored the importance of fostering a supportive digital learning environment to enhance technology-driven instructional practices. The study recommends targeted interventions to improve accessibility, digital literacy, and infrastructural support to optimize students’ engagement with online learning platforms. Future research should explore the moderating effects of demographic and institutional factors on students’ technology adoption.